Speleothems Reveal 500,000-Year History of Siberian Permafrost - Vaks, Anton; Gutareva, O.S.; Breitenbach, Sebastian F.M.; Avirmed, E.; Thomas, Alex L.; Osinzev, Alexander V.; Kononov, Alexander M.; Henderson, Gideon M. (Science, 2013)
ISSN:0036-8075 ISSN:1095-9203